India: Historical Beginnings & The Concept Of The Aryan
The book provides fresh insights into the beginnings of Indian history, and argues for a comparative study of various societies that co-existed during the period and their mutual interactions. A major contribution to historigraphy, the book familarises the reader with a broad-spectrum of current scholarly discussions on the issue.